(untitled) (Journal of Nepal Geological Society, 2000)
Tunnel and underground works of smaller dimensions were introduced in Nepal by the early miners during the 19th century. They applied their traditional technology to mine the ores of copper. Iron, lead, cobalt, and nickel. But, their activity virtually came to an end when these metals were easily available in the local market through the supply from India. Tunnelling for the 1 MW Tinau Hydropower Project done by Nepalese technician through the Siwalik rocks was a pioneering activity to convince the concerned institutions and technicians that tunnelling through hills and mountains of Nepal is technically feasible. There were fourteen operational tunnels and eleven test audits (36.16 km in total length) driven through different rocks and geological conditions in Nepal up to 1999. They have successfully dissected the Siwaliks, Midlands, and the Higher Himalaya irrespective of their geological conditions and rock types. At present, seven tunnel projects are under construction, which will augment an additional length of 28.436 km by the year 2000. Today, hydropower development without perception of a tunnel component is virtually impossible. It is also true for the supply of irrigation water in a year-round basis to the agricultural land of the Terai. A demand for tunnel works in the improvement of water supply system and road network is also emerging in urban areas like Kathmandu. The need of a 28 km long tunnel is identified in the Kathmandu-Melamchi Water Supply Project, which will be the first tunnel to supply drinking water in Nepal. Similarly, the Kathmandu-Hetaunda Direct Link Project will be the first of its kind to use tunnels of 3.8 km to 7.5 km in length.